2019
DOI: 10.1101/691097
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcription factor NF-κB in a basal metazoan, the sponge, has conserved and unique sequences, activities, and regulation

Abstract: Biological and biochemical functions of immunity transcription factor NF-κB in basal metazoans are largely unknown. Herein, we characterize transcription factor NF-κB from the demosponge Amphimedon queenslandica (Aq), in the phylum Porifera. Structurally and phylogenetically, the Aq-NF-κB protein is most similar to NF-κB p100 and p105 among vertebrate proteins, with an Nterminal DNA-binding/dimerization domain, a C-terminal Ankyrin (ANK) repeat domain, and a DNA binding-site profile more similar to human NF-κB… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 40 publications
(6 reference statements)
1
10
0
Order By: Relevance
“…Protist NF-κB proteins vary in domain structure and choanoflagellates show evidence of gene duplication Suga et al (4) reported the presence of a single gene encoding an NF-κB-like protein in C. owczarzaki (Co). The overall protein structure of Co-NF-κB is similar to most other basal NF-κB proteins known to date, in that it has an N-terminal RHD, followed by a glycine-rich region (GRR), and five C-terminal ANK repeats (15)(16)(17)(18). However, Co-NF-κB is larger than other NF-κB homologs, due primarily to additional residues C-terminal to the ANK repeats (Fig.…”
Section: Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“…Protist NF-κB proteins vary in domain structure and choanoflagellates show evidence of gene duplication Suga et al (4) reported the presence of a single gene encoding an NF-κB-like protein in C. owczarzaki (Co). The overall protein structure of Co-NF-κB is similar to most other basal NF-κB proteins known to date, in that it has an N-terminal RHD, followed by a glycine-rich region (GRR), and five C-terminal ANK repeats (15)(16)(17)(18). However, Co-NF-κB is larger than other NF-κB homologs, due primarily to additional residues C-terminal to the ANK repeats (Fig.…”
Section: Resultsmentioning
confidence: 80%
“…That is, in most metazoans, the activity of NF-κB is regulated at the posttranscriptional level, whereas in Aiptasia and corals, we have found that NF-κB mRNA levels and DNA-binding activity appear to be coordinately regulated, suggesting transcriptional regulation. That is, in Aiptasia, thermal bleaching causes transcriptional upregulation of NF-κB, which also results in increased protein expression of nuclear, (15)(16)(17). Moreover, induction of NF-κB DNA-binding activity and protein levels by loss of symbiosis in Aiptasia appears to be primarily a result of increased transcription of NF-κB and not due to induced ANK repeat degradation.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations